The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2009
DOI: 10.1111/j.1365-2230.2009.03247.x
|View full text |Cite
|
Sign up to set email alerts
|

Pigmentary demarcation lines associated with pregnancy

Abstract: We report three cases of pigmentary demarcation lines associated with pregnancy. In addition, we reviewed 19 cases including our 3 cases, which were reported in Japan. Most cases occurred during the latter period of pregnancy (after the seventh month), and the pigmentation faded spontaneously or disappeared a few months after delivery in all cases except one. Pigmentary demarcation lines are classified into five groups (types A-E). Of the 19 cases we reviewed, 2 cases showed lines of both types A and B, wherea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(20 citation statements)
references
References 6 publications
0
17
0
Order By: Relevance
“…Furthermore, the involved areas of the anterior thighs and knees in our case do not correspond to the innervation of S1 and S2. To our knowledge, there have been two reports on PDLs with erythematous changes3,8. Mild basal layer pigmentation was observed in previous reports of PDLs that examined the biopsies, histopathologically8.…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…Furthermore, the involved areas of the anterior thighs and knees in our case do not correspond to the innervation of S1 and S2. To our knowledge, there have been two reports on PDLs with erythematous changes3,8. Mild basal layer pigmentation was observed in previous reports of PDLs that examined the biopsies, histopathologically8.…”
Section: Discussionmentioning
confidence: 84%
“…Recently, it was suggested that these lines may occur on the face, and additional categories F, G, and H have been suggested2. Type B PDLs are more commonly associated with pregnancy, and are mostly known to occur after the seventh month of pregnancy3. We present a case of type B PDLs of pregnancy, with three interesting main features: 1) a relatively early onset at the end of the fourth month of pregnancy, 2) association of erythematous changes, and 3) unique distribution, involving both the anterior and the posterior aspects of the lower extremities.…”
Section: Introductionmentioning
confidence: 96%
“…In some cases, facial PDLs can merge with the periorbital pigmented circle. The skin biopsy specimen in PDLs (type B) shows a slight lymphocyte infiltration around vessels in the upper dermis with mild basal layer hyperpigmentation . In another study, basal and suprabasal pigmentation with mild pigment incontinence in papillary dermis was evident histologically; there may be only increased melanization .…”
Section: Diagnosismentioning
confidence: 91%
“…They may correspond to areas of peripheral cutaneous innervations, pigmentary mosaicism, or cutaneous nerve distribution . An enlarged uterus in the latter period of pregnancy may compress the peripheral nerves originating from the S1 and S2 levels of the spine and obstruct the innervated cutaneous microvasculature causing excessive pigmentation . Inflammation of cutaneous nerves during pregnancy has also been postulated as a cause.…”
Section: Pathogenesismentioning
confidence: 99%
“…The pigmentary change may be more obvious in the SOC population (Nakama et al 2009). Melasma (chloasma) is the most cosmetically disturbing form of hyperpigmentation and occurs during up to 75% of pregnancies (McHugh and Laurent 1989).…”
Section: Pigmentary Changesmentioning
confidence: 99%